PENGARUH TINGKAT PROLIFIKASI TERHADAP KADAR HEMATOLOGIS DOMBA BATUR - Andara, Ghaitza; Sumaryadi, Mas Yedi; Saleh, Dadang Mulyadi (ANGON: Journal of Animal Science and Technology, 2022)
Background. This research aimed to find out the effect of prolification levels on hematological profile in Batur sheep which includes erythrocyte, leukocytes, and hemoglobin levels. Materials and methods. The research material used 20 ewes of batur sheep with a minimum parity in 2 times and an average age of 3 years, then they were grouped into two groups of 10 each. The first change is low prolification (P1) with JAS = 1 and the second change is high prolification (P2) with JAS records ≥ 2. Grouping is done based on the results of interviews with breeders related to their reproductive history. Blood sampling of 1-2 ml through the jugular vein and poured into the EDTA vacuum tube then stored in the ice box to prevent plumping and damage of blood cells. Examination of hematological profiles is done using a hematology analyzer. Data is processed by using t-test unequal. Results. The results of statistical analysis showed that there was no significant difference (P>0.05) from the level of prolification to erythrocyte and hemoglobin counts, but has a significant difference (P<0.05) to the number of leukocytes in Batur sheep. Conclusion. It’s concluded that the levels of erythrocyte and hemoglobin were relatively similar between prolification levels, but leukocytes levels in low prolific were significantly higher than those of high prolific in Batur sheep.